Developing Traditional Public Revenues to Address the State Budget Deficit Libya as a Model (Al-Farooq Journal of Sciences, 2026)
This research examines the development of traditional public revenues as a mechanism to address the budget deficit in the Libyan state during the transitional period since 2011. It highlights that the fiscal imbalance has resulted from a widening gap between rising public expenditures and declining public revenues, alongside a heavy dependence on oil revenues and their associated volatility, which negatively affects fiscal stability. The increase in public expenditure is attributed to the expansion of the state’s economic and social role, higher investment and public service spending, and increased security-related expenditures under unstable political conditions. Administrative factors also play a significant role, including financial corruption, an inflated public sector workforce, and weak public financial management. On the revenue side, the decline is linked to the rigidity of the tax system, widespread tax evasion, and the excessive use of tax exemptions, in addition to the rentier nature of the Libyan economy and its reliance on oil as the primary source of public revenue. The study further analyzes traditional financing instruments used to cover the budget deficit, dividing them into ordinary revenues such as taxes, fees, and state domain income, and extraordinary revenues such as public borrowing and monetary issuance. It also highlights the legal and economic implications of these instruments, particularly the inflationary effects of monetary expansion and the long-term fiscal burdens associated with public debt. The research concludes that addressing Libya’s budget deficit requires comprehensive fiscal reform, including modernization of the tax system, rationalization of public expenditure, and diversification of revenue sources, while reducing reliance on oil revenues and non-traditional financing methods to ensure fiscal stability and sustainable economic development.